1994
DOI: 10.3354/meps104293
|View full text |Cite
|
Sign up to set email alerts
|

Predation by a dinoflagellate on a red microalga with a cell wall modified by sulfate and nitrate starvation

Abstract: The dlnoflagellate Crypthecodinium cohn~i was found to prey specifically on the unicellular red alga Porphyrjdum sp. and to contain enzymes that degrade its cell wall Cell wall production and conlposition of the alga are affected by nitrate and sulfate deprivation, the main changes being an increase in methylhexose and a decrease in glucose and xylose. When the dinoflagellate was fed with Porphyndium sp. having modified cell walls, fewer cells were ingested. Similarly, in chemosensory experiments it was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…Therefore, the effects of nitrogen and sulfate starvation on N-glycosylation of the 66-kDa protein were found to be similar. These observations are in agreement with former studies [55][56][57], where it was reported that in both starvation conditions, the cells directed most of their energy toward the synthesis of cell-wall polysaccharide, an activity that is probably important for its survival. The decrease in 66-kDa protein production and in its N-glycan composition in both starvation conditions was expected, because under these conditions, the cells inhibit protein synthesis to the benefit of polysaccharide production.…”
Section: Effect Of Growth Conditions On the Cell-wall Glycoproteins Asupporting
confidence: 83%
See 1 more Smart Citation
“…Therefore, the effects of nitrogen and sulfate starvation on N-glycosylation of the 66-kDa protein were found to be similar. These observations are in agreement with former studies [55][56][57], where it was reported that in both starvation conditions, the cells directed most of their energy toward the synthesis of cell-wall polysaccharide, an activity that is probably important for its survival. The decrease in 66-kDa protein production and in its N-glycan composition in both starvation conditions was expected, because under these conditions, the cells inhibit protein synthesis to the benefit of polysaccharide production.…”
Section: Effect Of Growth Conditions On the Cell-wall Glycoproteins Asupporting
confidence: 83%
“…For example, growing Porphyridium sp. in a medium deprived of nitrate and sulfate enhances production and solubilization of the polysaccharide [14]. Moreover, these conditions have also been shown to change polysaccharide compositions [14].…”
Section: Chemical Studiesmentioning
confidence: 99%
“…Furthermore, a mannose-rich cell wall glycoprotein on the red microalga Porphyridium sp. is suspected to act as a biorecognition site for its specialist predator, a Crypthecodinuim cohnii-like protozoan (23,26,27). The possibility that lectin-carbohydrate interactions might also be implicated in prey biorecognition and/or selection is clearly feasible, but now requires further investigation.…”
mentioning
confidence: 99%
“…Some 16 years ago it was proposed that certain protozoa might use 'contact chemoreceptors' to discern the profitability of different prey items on the basis of their cell-surface biochemical composition (28). However, exploration of molecular-level signalling and recognition processes between predatory and prey cells has only been pursued more recently (23,26,27,32). Of significance are the recent findings of Wootton et al (32) who identify a mannose-specific feeding receptor on the phagotrophic protozoan Oxyrrhis marina -a marine species in which selective feeding is well-documented (7,10,16,29).…”
mentioning
confidence: 99%
“…species -Crypthecodinium cohnii -shows strong positive chemotaxis towards polysaccharides derived from its specialist prey species -the marine microalga Porphyridium (29). Given the specificity of S. microadriaticum and C. cohnii, it is reasonable to infer that the chemosensory apparatus and responses of both could be highly refined.…”
mentioning
confidence: 99%